Perlindungan Hukum Terhadap Hak Upah Lembur Pekerja/Buruh - Kusumawati, Mustika Prabaningrum (Jurnal Ilmiah Penegakan Hukum, 2024)
Problems related to worker/labor protection that often occur in the field are related to working time where employers employ workers/laborers beyond working time regulations by ignoring the rights of workers/laborers such as the right to overtime wages that should be received. This research is normative legal research with a descriptive analytical nature using a literature and field approach. The analysis of the data obtained in this research was carried out qualitatively. The results of the research show that a form of legal protection for workers/laborers is that if the entrepreneur wants the workers/laborers to work overtime, the workers/laborers who carry out overtime work are entitled to overtime pay, have the right to adequate rest time and are entitled to receive food and drink of at least 1400 kilo calories. cannot be replaced with money. The legal action that workers/laborers can take if their rights are not fulfilled is through bipartite efforts. However, if this effort fails, you can take mediation and if it still fails, you can file a lawsuit at the Industrial Relations Court.